The rational Southerner : black mobilization, republican growth, and the partisan transformation of the American South - Hood, M. V.; Kidd, Quentin; Morris, Irwin L. (Irwin Lester), 1967- (New York ; Oxford : Oxford University Press, 2012)
What drove the transformation of post-World War II politics in the South? In The Rational Southerner, M. V. Hood, Quentin Kidd, and Irwin L. Morris develop a theory of relative advantage to explain why whites fled the Democratic Party and what propelled black political mobilization. Collating decades of data, the authors demonstrate that race was, and is, the chief force behind political change in the region.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Republican Party (U.S. : 1854- ); Democratic Party (U.S.); Political culture -- Southern States; African Americans -- Southern States -- Politics and government; Racism -- Southern States; Party affiliation -- Southern States; Southern States -- Politics and government; Southern States -- Race relations